The contribution of e-banking to the competitive advantage of banking institutions in Algeria: Case Study of Agricultural and Rural Development Bank (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The importance of the study stems from the fact that it deals with a very important subject, namely, the pivotal role played by E-banking in achieving the competitive advantage of the banking institutions operating in Algeria. By adopting the banking institution and adopting the elements of the electronic marketing mix and developing it as required by the environment The banking system of developments will inevitably be able to achieve excellence from its competitors as each of these elements have an important role in achieving competitive advantage, we relied in this study on studies and research that directly affect the problem of the study and we have put Estep In order to activate the contribution of e-banking in achieving competitive advantage, it is necessary to develop the website of the banking institution and make it more secure and reliable to achieve customer satisfaction, and not only as a website that provides information about the services available to the banking institution , And the promotion of security, confidentiality and privacy at the level of banking institutions to protect the information and transactions of customers and thus gain their confidence, which leads to the expansion of market share and achieve excellence.